Cultura organizacional en la gestión administrativa de la compañía Santacruz Taday construcciones CIA. LTDA, en la parroquia Ducur, cantón Cañar, provincia Cañar, año 2024 - Santacruz Yupa, Flor Milena (2025)
The research titled “Organizational Culture in the Administrative Management of Santacruz Taday Construcciones Cía. Ltda., in the Parish of Ducur, Cañar Canton, Cañar Province, Year 2024” aims to analyze how organizational culture influences the administrative management of the mentioned company during the year 2024. The hypothesis suggests that organizational culture does indeed influence the administrative management of Santacruz Taday Construcciones Cía. Ltda. A mixed-methodology approach was utilized, including field research, bibliographic review, and descriptive analysis. Data was collected through surveys and interviews with the company's employees. The findings revealed that a weak organizational culture negatively affects administrative management, leading to issues such as poor internal communication and project delays. The conclusions indicate that strengthening the organizational culture is crucial for improving administrative efficiency and staff performance. It is recommended to continue developing and consolidating a strong organizational culture to achieve effective and efficient administrative management.